Indocyanine green fluorescence-guided sentinel node biopsy: a meta-analysis on detection rate and diagnostic performance - Xiong, Lingyun; Gazyakan, Emre; Yang, W.; Engel, Holger; Hünerbein, M.; Kneser, Ulrich; Hirche, Christoph (European journal of surgical oncology, 2014)
Background - Indocyanine green (ICG) fluorescence-guided sentinel node biopsy (SLNB) has been successfully employed in various kinds of tumors. Clinical results of previous studies on this technique are at different levels of evidence. This Meta-analysis was conducted to provide a more precise estimation on its clinical performance. - Methods - Eligible studies were identified from systematical PubMed and EMBASE searches; data were extracted. A Meta-analysis was performed to generate pooled detection rate, sensitivity, specificity, diagnostic odds ratio (DOR) and summary receiver operator characteristic curves. - Results - Fifteen published articles were included. Clinical data of 513 patients were obtained. The pooled detection rate, the pooled sensitivity, the pooled specificity, the pooled DOR and their 95% confidence intervals (95% CI) were 0.96 (0.91-0.99), 0.87 (0.79-0.92), 1.00 (0.99-1.00) and 150.13 (57.42-392.56), respectively. Significant heterogeneities existed among studies. Significant publication bias was found in detection rate. The concentration < 5 mg/ml subgroup and the injected volume ≥2 ml subgroup had higher DORs, sensitivities and detection rates than the concentration ≥ 5 mg/ml subgroup and the injected volume <2 ml subgroup, respectively. - Conclusion - Based on this Meta-analysis, this technique could be valued promising for detecting the presence of LN metastases. ICG injection with reduced concentration and larger volume may provide improved performance.